2002
DOI: 10.1256/0035900021643700
|View full text |Cite
|
Sign up to set email alerts
|

Equatorial waves in temperature in the altitude range 4 to 70 km

Abstract: SUMMARYUsing altitude pro les of temperature in the range 4 to 70 km derived from Mesosphere-StratosphereTroposphere radar and lidar observations at Gadanki (13.5 ± N, 79.2 ± E) from 18 January 1999 to 5 March 1999, characteristics of equatorial waves are studied. Two-dimensional Fourier-transform analysis of the temperature pro les is carried out to identify the periodicities and their vertical wave numbers. From the characteristics obtained, equatorial slow Kelvin waves with periodicities 15.7 d, 9.4 d, 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
0
18
1
1
Order By: Relevance
“…In the summer seasons there were a couple of days with cloudy skies (during the observation period) which were not included in the analysis. It may be noted here that the method of Revathy et al (1996) has been successfully used for the studies on the diurnal variation of troposphere temperatures and equatorial waves (Revathy et al, 2001;Krishna Murthy et al, 2002). The temperature profiles thus obtained and the vertical wind profiles (from MST radar) form the basic data for obtaining the tropopause altitude (and temperature), according to its definitions given above.…”
Section: Data and Analysismentioning
confidence: 99%
“…In the summer seasons there were a couple of days with cloudy skies (during the observation period) which were not included in the analysis. It may be noted here that the method of Revathy et al (1996) has been successfully used for the studies on the diurnal variation of troposphere temperatures and equatorial waves (Revathy et al, 2001;Krishna Murthy et al, 2002). The temperature profiles thus obtained and the vertical wind profiles (from MST radar) form the basic data for obtaining the tropopause altitude (and temperature), according to its definitions given above.…”
Section: Data and Analysismentioning
confidence: 99%
“…They reported increased Kelvin-wave variance accompanying the descent of the westerly phase of the QBO, with the largest amplitudes occurring in the westerly shear zone. Equatorial wave characteristics have been reported in several studies (Salby et al, 1984;Dhaka et al, 1995;Krishna Murthy et al, 2002;Fujiwara et al, 2003) using temperature observations. Tsuda et al (1994a,b) conducted an observational campaign for 24 days in Watukosek, Indonesia (7.6 • S, 112.7 • E).…”
Section: Introductionmentioning
confidence: 85%
“…These waves showed downward phase progression with an average vertical wavelength of 10 km. More recently, Krishna Murthy et al (2002), using radar and Lidar data, identified equatorial slow Kelvin waves with different periodicities from 6-16 days in the troposphere and stratosphere regions. They found that equatorial waves modulate tropical tropopause temperature and altitude.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, two unique campaigns of coordinated measurements have been conducted for studies on equatorial waves with emphasis on estimation of momentum fluxes. The first one involved 45 days of simultaneous measurements by co-located Rayleigh lidar and Indian MST radar (Krishna Murthy et al, 2000) and the second one employing lidar, MST radar and rockets (Krishna Murthy et al, 2002).…”
Section: Introductionmentioning
confidence: 99%